2019
DOI: 10.1155/2019/7457385
|View full text |Cite
|
Sign up to set email alerts
|

Gender Difference of the Relationship between Arterial Stiffness and Blood Pressure Variability in Participants in Prehypertension

Abstract: Aim. The association of pressure load with elasticity in vascular system has not been studied fully. We proposed a hypothesis whether gender could modify the association of blood pressure variability (BPV) and arterial stiffness assessed by carotid-femoral pulse wave velocity (CF-PWV) in prehypertensive patients. Methods. 24h ambulatory blood pressure monitoring (24h-ABPM) and CF-PWV were measured in 723 participants with prehypertension. Univariate and multivariate regression analyses of these clinical and bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
6
0
1
Order By: Relevance
“…10 A possible explanation for this could be due to arterial stiffness being greater in males than in females. 33,34 The current study shows that after exclusion of hypertensive participants, higher HDL-C became associated with lower BP in males, suggesting that hypertension, which could worsen arterial stiffness, 35 may contribute to the sex difference in the association between HDL-C and BP.…”
Section: Discussionmentioning
confidence: 60%
“…10 A possible explanation for this could be due to arterial stiffness being greater in males than in females. 33,34 The current study shows that after exclusion of hypertensive participants, higher HDL-C became associated with lower BP in males, suggesting that hypertension, which could worsen arterial stiffness, 35 may contribute to the sex difference in the association between HDL-C and BP.…”
Section: Discussionmentioning
confidence: 60%
“…To the best of our knowledge, this is the first study that demonstrates differences in cf-PWV between genders in nearly all homogeneous patients in terms of classic comorbidities such as hypertension, diabetes mellitus, metabolic syndrome, chronic obstructive pulmonary diseases, and heart failure among Polish geriatric patients and shows differences in the impact of individual risk factors on the cfPWV value in gender groups. There are some studies that have assessed the relationship between arterial stiffness and gender, but most of them have been conducted in the younger population [23][24][25][26][27]. No significant difference was found for PWV, arterial age, and augmentation index in an analysis of gender and arterial stiffness among smokers (mean age 38).…”
Section: Resultsmentioning
confidence: 96%
“…In participants with prehypertension (mean age 59.76 + 12.37) selected from the BEST study, males had higher PWV than females (10.89 vs. 10.33 m/s, respectively). However, differences in the distribution of other CV risk factors were observed, such as: (1) age, BMI, FPG, UA, and homocysteine being higher in males compared with females, and (2) TC, HDL-C, and LDL-C being higher in females [24]. In a study conducted among the Tallinn population aged 20-65, a higher PWV was observed in hypertensive men aged equal to or above 50 years, as well as in hypertensive women with diabetes and in apparently healthy women with increased apolipoprotein B [25].…”
Section: Resultsmentioning
confidence: 97%
“…Twenty-four-hour ambulatory blood pressure monitoring can automatically and continuously record blood pressure changes within 24 h, including daytime and nighttime systolic blood pressure, diastolic blood pressure, mean blood pressure, maximum and minimum blood pressure, etc. Blood pressure variability directly reflects the stiffness and buffering function of blood vessels and is closely related to the occurrence of CVD, such as cognitive impairment [ 55 , 56 ]. Dynamic electrocardiogram (ECG) was first developed by Holter in 1957.…”
Section: Evaluation Parameters Of Endothelial Functionmentioning
confidence: 99%